Commodifying piety and styling masculinity in "Kahf’s Jalan yang Kupilih" campaign - KUSUMANINGTYAS, SHELA (Jurnal Studi Komunikasi, 2026)
This study investigates the commercialisation of religion and masculinity in the Indonesian men's grooming campaign Kahf: Jalan yang Kupilih. The statement considers two key issues: (1) the Islamic symbols utilised in advertisements and their purpose in branding, and (2) the model of Muslim masculinity constructed through those symbols. The analysis relies on Roland Barthes' semiotics to interpret denotation, connotation, and myth as naturalised ideology, and it utilises Theodor Adorno's critique of the culture industry to understand standardisation and market forces driving representation. The study employs a qualitative semiotic analysis of eight video commercials on Kahf's official YouTube channel, which involves coding visual elements such as setting, gesture, and costume, and auditory elements including voice-over, dialogue, and music, and triangulates this with existing literature on Islamic advertising. Research suggests that ritual symbols such as ablution, prayer stances, Qur'anic/hadith verses, and Middle Eastern architectural settings are reinterpreted as markers of personal style that link devotion to consumer goods and company values. The campaign promotes a uniform masculine ideal characterised by cleanliness, composure, discipline, a global outlook, and a focus on family, while limiting the scope of acceptable religious and gender identities. Scenes of ablution, facial cleansing, and prayer among Qatar's iconic landmarks, and hadith panels in modern public areas, juxtapose spiritual purity with consumer preference and portray faith as a desirable lifestyle. This study enhances advertising semiotics by describing the way Islamic symbolism is utilised in narratives about men's grooming, and it also clarifies the empirical connections between visual representations of piety and branded masculinity.